ANALYSIS OF CHARACTER BUILDING CONTENT ON SCIENCE TEXTBOOK OF THE 2013 CURRICULUM AND TEACHERS’S IMPLEMENTATION PERFORMANCES - Irawan, Bony (Jurnal Kiprah, 2016)
Implementation of the 2013 curriculum is an attempt to halt the moral decadency of Indonesian youth and to provide legal and systematic baseline on character building through education. Key factor determining the success of the new curriculum in achieving it’s grand purpose is the support of a textbook as the most visible and most referred component of a curriculum. The study aims to scrutiny the 2013 curriculum’s official science textbook for junior high school and documented the character building indicators contained inside, explicit and implicitly, and observes the learning process to acquire the pattern of it’s implementation by the teachers. Any texts, activities, tasks, suggestions, and graphics that will lead to character building contained in the selected chapter of the book were tabulated to be compared with curriculum’s objectives. Thus, providing insight to the textbook’s congruity on supporting the curriculum’s objectives. Classroom learning process is observed to obtain the implementation patterns of the character building attempt by the teacher. This is a descriptive qualitative study. Subjects of the study was selected by purposive sampling technique. Data obtained through documentation and observation technique. Results shows the textbook contained very few material that could help build student’s character. The textbook contained only 25% of the character building indicators. The official textbook focused heavily on science subject and doesn’t run in accordance with curriculum’s purpose on character building. The lack of character building indicators also diminished the textbook’s guidance role to help teacher develops a balanced learning between subject matters and character building, as the new curriculum required. Implementation of character building in learning process by inexperienced student teacher shows a striking resemblence with the textbook at 26%. Proving the textbook unreliable as a guidance in developing a balanced learning between subject matter and character building.